2010
DOI: 10.1002/jcc.21662
|View full text |Cite
|
Sign up to set email alerts
|

A novel predictive model for formation enthalpies of Si and Ge hydrides with propane‐ and butane‐like structures

Abstract: Butane- and propane-like silicon-germanium hydrides and chlorinated derivatives represent a new class of precursors for the fabrication of novel metastable materials at low-temperature regimes compatible with selective growth and commensurate with the emerging demand for the reduced thermal budgets of complementary metal oxide semiconductor integration. However, predictive simulation studies of the growth process and reaction mechanisms of these new compounds, needed to accelerate their deployment and fine-tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The bond lengths obtained from our simulations follow the expected trends and are in excellent agreement with those obtained by other authors, and those reported in our prior work on trigermane and tetragermane using slightly smaller basis sets and coarser grids. For example, the shortest Ge–Ge bond lengths (2.444 Å) typically occur between −GeH 3 and −GeH 2 – moieties, while slightly longer values (2.450 Å) prevail between −GeH 3 and −GeH–, or adjoining −GeH 2 – groups.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The bond lengths obtained from our simulations follow the expected trends and are in excellent agreement with those obtained by other authors, and those reported in our prior work on trigermane and tetragermane using slightly smaller basis sets and coarser grids. For example, the shortest Ge–Ge bond lengths (2.444 Å) typically occur between −GeH 3 and −GeH 2 – moieties, while slightly longer values (2.450 Å) prevail between −GeH 3 and −GeH–, or adjoining −GeH 2 – groups.…”
Section: Resultssupporting
confidence: 91%
“…According to the thermochemical data in Table the most stable species is i -Ge 4 H 10 , which is consistent with the trends observed in classic butane, where simple gas phase models predict a room temperature equilibrium ratio of ∼9:1 for i -C 4 H 10 / n -C 4 H 10. The calculated vibrational spectra of the tetragermane isomers are shown in Figure (top and bottom corresponding to low- and high-frequency regimes), where they are compared with an experimental spectrum of a gas sample. The latter was obtained from a freshly distilled bulk liquid aliquot which was previously characterized by NMR spectroscopy, showing a mixture of 85% n -Ge 4 H 10 and 15% of i -Ge 4 H 10 , where the 85% can, in principle, be further subdivided into “trans” and “gauche”, which can not be clearly resolved by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structures and corresponding thermodynamic data for all isomers are summarized in Table 1. The calculated bond lengths exhibit trends very similar to those the we previously reported for tetragermane, 32,34 whose isomers share many of the same geometry and bonding motifs with pentagermane. For example, the shortest Ge-Ge bond lengths (2.444-2.446 Å) are designated as "a" in our table, and connect terminal -GeH 3 and -GeH 2moieties.…”
Section: Resultssupporting
confidence: 84%
“…16 As in the case of the Ge 4 H 10 , the Si 4 H 10 bond lengths calculated from our simulations are in general excellent agreement with those obtained by other authors, and in our prior work and follow expected trends. 19,20 The shortest Si−Si bond lengths (2.351 Å) typically occur between −SiH 3 and −SiH 2 − moieties, while slightly longer values (2.355 Å) are found between −SiH 3 and −SiH−, or adjoining −SiH 2 − groups. In analogy with the Ge analogue, the Si−H bond lengths are also found to follow the expected increasing trend 1.483, 1.486, and 1.490 Å for the −SiH 3 , −SiH 2 −, and −SiH− moieties, respectively.…”
Section: → + 2ge Hmentioning
confidence: 99%